ESG-financial performance in the Gulf region: a bidirectional examination - Tavares, Rodrigo; Stefanescu-Cuntze, Catalina; Sá, Catarina (Sustainable Communities, 2025)
Purpose Scholarly attention towards the Gulf Cooperation Council (GCC) region (Bahrain, Kuwait, Oman, Qatar, Saudi Arabia, and the United Arab Emirates) has been limited due to its various unique features, making it an ideal testing ground for ESG practices. This paper is the first scholarly endeavor to comprehensively analyze the bidirectional causal relations between ESG and financial performance in the Gulf region.Materials and methods This study analyzes a sample of 54 publicly traded firms, using firm-level monthly observations of ESG scores and stock prices from January 2009 to May 2023. Stock returns—measured contemporaneously and with lags of 12, 18, and 24 months—serve as the indicator of financial performance. The analysis includes market returns, company size, and industry as control variables, consistent with established literature. Market returns represent the overall performance of the stock market during the relevant periods. All financial data were obtained from the Bloomberg Terminal, and ESG data were collected from ESG Book.Results The statistical analysis of the impact of both aggregated (ESG) and individual (E, S, and G) scores on stock returns indicate a weak relationship between sustainability and financial performance in the Gulf region. The assessment of public companies in the region demonstrates that stock markets display minimal responsiveness to changes in ESG metrics, indicating that improvements in ESG scores do not translate into higher stock returns. Similarly, the analysis of reverse causality—assessing whether financial performance influences future ESG performance—shows a weak association. While there is a slight indication that some firms with better stock returns may allocate some profits toward governance and environmental initiatives, this relationship is marginal and lacks strong statistical support.Conclusions Both the direct and reverse relationships between ESG scores and financial performance are weak, underscoring that ESG factors have yet to become significant drivers or consequences of stock returns in the Gulf region. These findings highlight the need to explore whether ESG progress is instead shaped by state leadership, regulatory mandates, and alignment with national strategic priorities, rather than by market-driven forces.